Assessing global and regional public interest in home dialysis modalities from 2004 to 2024 - Thongprayoon, Charat; Wathanavasin, Wannasit; Suppadungsuk, Supawadee; Davis, Paul W.; Miao, Jing; Mao, Michael A.; Craici, Iasmina M.; Qureshi, Fawad; Cheungpasitporn, Wisit (Frontiers in Nephrology, 2024)
Background and objectivesHome dialysis (peritoneal dialysis and home hemodialysis) is an important renal replacement therapy modality option for patients with end-stage kidney disease. As the Internet has become a primary source for healthcare information, this study aimed to analyze the global and regional interests in home dialysis using Google Trends™ data from January 2004 to March 2024.Design, setting, participants, and measurementsA comprehensive analysis was conducted using Google Trends™ with the search terms “Peritoneal Dialysis” and “Home Hemodialysis.” This study extracted worldwide trends and detailed regional interests within the United States. Interest levels were quantitatively assessed based on Google Trends™ indices, providing insights into temporal patterns and geographical distributions of public interest.ResultsThe study found a fluctuating pattern of global interest in Peritoneal Dialysis, with peak interest in March 2022 and lowest interest in December 2008. The most recent data from March 2024 showed significant interest level of 94, indicating a new upward trend. Mexico exhibited the highest relative interest in Peritoneal Dialysis. Within the United States, Tennessee demonstrated the highest interest. For Home Hemodialysis, the peak interest was in July 2004. The most recent data from March 2024 showed a modest increase in interest. The United States led in highest relative interest for Home Hemodialysis, followed by Australia, Canada, and the United Arab Emirates. Within the United States, Mississippi demonstrated the highest interest.ConclusionsThis study offers crucial insights into the global and regional landscape of interest in home dialysis modalities over time, highlighting the significance of leveraging online platforms to increase public awareness, education, and engagement home dialysis modalities. By understanding the temporal and geographical patterns of interest, healthcare providers, policymakers, and patient advocacy groups can develop targeted strategies to better promote the benefits of home dialysis, address knowledge gaps, and improve access to these life-sustaining treatments.